THE ROLE OF SOCIAL MEDIA IN SHAPING CHRISTIAN CHARACTER AMONG GENERATION Z - Resti; Esterani; Daniel Nianda; Theodorus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The 21st century has witnessed a radical transformation in human communication ecology, with social media evolving from mere connection platforms into a primary lifeworld for young people. Generation Z, growing up in an intrinsically digital environment, internalizes the logic, norms, and rhythms of social media into their identity construction. This study employs a Systematic Literature Review (SLR) method to analyze 32 empirical studies (2019-2024) exploring the role of social media in shaping Christian character among Generation Z. The findings reveal a dual formative role: social media acts as a Curated Sanctuary, providing unprecedented access to spiritual resources, communities, and role models, while simultaneously functioning as an Algorithmic Arena that fosters performative piety, theological reduction, and value conflicts. In response, Generation Z demonstrates active agency through negotiation strategies like content curation, compartmentalization, and digital fasting, leading to the formation of a hybrid habitus. This review proposes a Critical Digital Discipleship Framework as an integrative model emphasizing theological digital literacy, intentional curation, and embodied integration to guide effective character formation in the digital age.